Studying food systems as embedded, sensory phenomena - Morgan, Caitlin B. (Frontiers in Sustainable Food Systems, 2023)
This article offers a theoretical foundation for pursuing transdisciplinary food systems research, informed by deep sustainability and equity, across various scales of the system. It weaves together ontologically aligned, food-relevant social theory from ecofeminism, agroecology, ecological economics, systems theory and food systems scholarship, sensory studies, geography, and sociology. The epistemologies and associated methodologies of this literature all take seriously the physical laws of nature, while also recognizing that knowledge is situated in persons and places, and that people's experiences of the world are an important part of what we can know. They all recognize the urgent need to reorient Western mental modes and their destructive, attendant material relationships. Epistemological integration rests upon ontological convergence of embeddedness, embodiment, and the context for change, calling for a methodological approach of ethnographic, qualitative, and sensory research. No conception of the food system is complete without attending to the visceral, human experiences that shape it. Embeddedness and embodiment therefore offer an avenue for connecting information across different scales of the system, from the individual to the biosphere, allowing for the macro level to help make sense of the micro, and for the micro to reflect, resist, and alter the macro. Here, a new and better world is imagined and created through our bodies, in dialogue with and resistant to hegemonic power, and sensory research is key to understanding how things must and could change.